Myricetin prevents high molecular weight Aβ1-42 oligomer-induced neurotoxicity through antioxidant effects in cell membranes and mitochondria - Kimura, Atsushi Michael; Tsuji, Mayumi; Yasumoto, Taro; Mori, Yukiko; Oguchi, Tatsunori; Tsuji, Yuya; Umino, Masakazu; Umino, Asami; Nishikawa, Toru; Nakamura, Shiro; Inoue, Tomio; Kiuchi, Yuji; et al. (Free radical biology & medicine, 2021)
Excessive accumulation of amyloid β-protein (Aβ) is one of the primary mechanisms that leads to neuronal death with phosphorylated tau in the pathogenesis of Alzheimer's disease (AD). Protofibrils, one of the high-molecular-weight Aβ oligomers (HMW-Aβo), are implicated to be important targets of disease modifying therapy of AD. We previously reported that phenolic compounds such as myricetin inhibit Aβ1-40, Aβ1-42, and α-synuclein aggregations, including their oligomerizations, which may exert protective effects against AD and Parkinson's disease. The purpose of this study was to clarify the detailed mechanism of the protective effect of myricetin against the neurotoxicity of HMW-Aβo in SH-SY5Y cells. To assess the effect of myricetin on HMW-Aβo-induced oxidative stress, we systematically examined the level of membrane oxidative damage by measuring cell membrane lipid peroxidation, membrane fluidity, and cell membrane potential, and the mitochondrial oxidative damage was evaluated by mitochondrial permeability transition (MPT), mitochondrial reactive oxygen species (ROS), and manganese-superoxide dismutase (Mn-SOD), and adenosine triphosphate (ATP) assay in SH-SY5Y cells. Myricetin has been found to increased cell viability by suppression of HMW-Aβo-induced membrane disruption in SH-SY5Y cells, as shown in reducing membrane phospholipid peroxidation and increasing membrane fluidity and membrane resistance. Myricetin has also been found to suppress HMW-Aβo-induced mitochondria dysfunction, as demonstrated in decreasing MPT, Mn-SOD, and ATP generation, raising mitochondrial membrane potential, and increasing mitochondrial-ROS generation. These results suggest that myricetin preventing HMW-Aβo-induced neurotoxicity through multiple antioxidant functions may be developed as a disease-modifying agent against AD. [Display omitted] •Myricetin suppresses neurotoxicity by high molecular weight amyloid β oligomers.•The therapeutic target is oxidative stress at the cell membrane and mitochondria.•It not only works as an antioxidant but boosts the antioxidant function of neurons.•Myricetin may be developed as a disease-modifying agent for Alzheimer's disease.